Cross-cultural Validity and Reliability of the Recalled Parental Rearing Behavior Questionnaire - Seongmi MOON; Dong Hee KIM; Yu-Mi IM; Sunhee LEE (Tehran University of Medical Sciences, 2018)
Cross-cultural Validity and Reliability of the Recalled Parental Rearing Behavior Questionnaire